2018
DOI: 10.1111/mcn.12599
|View full text |Cite
|
Sign up to set email alerts
|

Innovative optimization of ready to use food for treatment of acute malnutrition

Abstract: Treatment of acute malnutrition typically requires the provision of ready-to-use food (RUF). Common RUF is effective but expensive, being manufactured from costly ingredients, and shipped worldwide from few global suppliers. I developed a linear programming tool to create RUF optimized for low cost using locally grown crops while maintaining necessary nutritional goals and other constraints. My tool utilizes a database of the nutritional value, price, and water efficiency of suitable ingredients and allows adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In some recent reviews (Brixi, 2018; Weber et al., 2017) and papers (Owino, Irena, Dibari, & Collins, 2014), it was reported that several RUTF formulations were proposed in several countries, such as Ethiopia, Ghana, Pakistan, and India, containing different legumes (almond, lentil, and soy), cereals (maize and oat), other oils (canola, rapeseed, coconut, and sunflower), and different forms of whey (acid whey milk and whey protein concentrate). In all the alternative RUTF formulations proposed, the inclusion of a vitamin and mineral premix was necessary, to ensure a balanced micronutrient intake of the final product.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some recent reviews (Brixi, 2018; Weber et al., 2017) and papers (Owino, Irena, Dibari, & Collins, 2014), it was reported that several RUTF formulations were proposed in several countries, such as Ethiopia, Ghana, Pakistan, and India, containing different legumes (almond, lentil, and soy), cereals (maize and oat), other oils (canola, rapeseed, coconut, and sunflower), and different forms of whey (acid whey milk and whey protein concentrate). In all the alternative RUTF formulations proposed, the inclusion of a vitamin and mineral premix was necessary, to ensure a balanced micronutrient intake of the final product.…”
Section: Introductionmentioning
confidence: 99%
“…In all the alternative RUTF formulations proposed, the inclusion of a vitamin and mineral premix was necessary, to ensure a balanced micronutrient intake of the final product. However, the use of country‐specific formulations had the potential to increase the practice of community‐based treatments, therefore, reducing the morbidity and mortality of severe acute malnutrition (SAM) in settings, where RUTF was not widely used (Brixi, 2018; Weber et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the versatility of the approach adopted here, it will be possible to expand and improve the database in order to find better and newer solutions, and it may also be possible to adapt the approach to specific contexts (such as agroecological variations) and specific populations [such as severe/moderate acute malnutrition, for instance ( 50 , 51 )]. This approach could provide valuable guidance to manufacturers when developing products adapted to the shift toward plant-based diets, and identifying innovative plant protein sources.…”
Section: Discussionmentioning
confidence: 99%
“…To this date, few solutions using this approach are available to develop new food products. Brixi ( 20 ) created an algorithm to formulate “ready to use food for the treatment of acute malnutrition” by minimizing the cost of the 26 raw materials in the dataset while satisfying the imposed nutritional criteria, crop water footprint, and ensuring a PDCAAS > 95, whereas De Carvalho et al ( 21 ) programmed an algorithm to support the formulation of low-cost porridges nutritionally suitable for 1–2-year-old children living in rural Mozambique, including a constraint for protein quantity (but not quality).…”
Section: Introductionmentioning
confidence: 99%